2019
DOI: 10.4401/ag-8253
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and isotopic signature of groundwater in the Santa Ninfa karst system and possible inferences on neotectonics

Abstract: The Santa Ninfa karst system is an area strongly controlled by tectonics, whose intense fracturing gave rise to the formation of a large number of cavities that foster the drainage of water. The hydrogeochemical characters of groundwater circulating in this aquifer, together with its isotopic signature, were investigated in detail. The chemistry of groundwater reflects the nature of the rocks hosting the aquifers, constituted by primary and diagenetic selenitic gypsum, salts, and gypsumarenite, whose dissoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In such karst areas, groundwater seepage is complicated, and karst caves are developed in the karst area. Favara R [3] believes that the karst system is an area that is strongly controlled by structure, and the fault has formed favorable drainage holes; the researcher discusses the relationship between geochemical monitoring of the Santa Ninfa karst aquifer and earthquake seismic generating processes. Ivanik O [4] found that groundwater is guided by the bottom of the syncline, and made hydrological simulations of upwellings using a mathematical rainfall runoff model to obtain the law of water balance.…”
Section: Introductionmentioning
confidence: 99%
“…In such karst areas, groundwater seepage is complicated, and karst caves are developed in the karst area. Favara R [3] believes that the karst system is an area that is strongly controlled by structure, and the fault has formed favorable drainage holes; the researcher discusses the relationship between geochemical monitoring of the Santa Ninfa karst aquifer and earthquake seismic generating processes. Ivanik O [4] found that groundwater is guided by the bottom of the syncline, and made hydrological simulations of upwellings using a mathematical rainfall runoff model to obtain the law of water balance.…”
Section: Introductionmentioning
confidence: 99%